Дослідження захисту VPN з використанням технології Kill Switch - Юркевич, М. О. (ХНУРЕ, 2024)
This research investigates the effectiveness and implications of VPN protection augmented by Kill Switch technology, exploring its capacity to fortify digital privacy, prevent data exposure, and bolster overall cybersecurity in an increasingly interconnected digital landscape.
Keywords: технологія Kill Switch; захист VPN